Habitats, agricultural practices, and population dynamics of a threatened species: The European turtle dove in France. (October 2022) - Sauser, Christophe; Commagnac, Loïc; Eraud, Cyril; Guillemain, Matthieu; Morin, Sophie; Powolny, Thibaut; Villers, Alexandre; Lormée, Hervé
Abstract: Agricultural changes in recent decades have led to a widespread loss of biodiversity, with habitat loss considered as the main factor in the decline. The European turtle dove is one of the farmland birds that has declined markedly in Europe, leading the IUCN to downgrade its status in 2015 from "Near Threatened" to "Vulnerable". Knowledge of how habitat factors and agricultural practices influence the turtle dove population is crucial for the conservation of this species through the implementation of targeted measures. Here we investigate how foraging and nesting habitats influence the abundance of turtle doves at national and regional scales, using a 23-year dataset from point counts carried out throughout France, a stronghold country for this species during the breeding season. We found that turtle dove abondance was positively affected by fallow lands, both at national and regional scales. Turtle dove abundance was also negatively affected by fodder crop area at national scale, but the effect was detected in only four of the 13 French regions. We also showed that an increase in hedgerows length had a positive effect on turtle dove abundance. On the other hand, forest edges length showed a bell-shaped trend, suggesting that an increase in forest edges length may have a favourable effect on turtle dove abundance only up to a given threshold. We suggest that targeted conservation measures combining an increase in fallow lands and hedgerows length could allow the stabilisation or even an increase in turtle dove abundance in France, but also in European countries with similar landscapes. Highlights: The general decline of turtle dove in France is less marked in the Mediterranean region. The decline in fallow land area is partly responsible for the decline of the turtle dove population. Increase in fodder crop area leads to a decrease in breeding turtle dove abundance. Increasing hedgerows may benefit to the turtle dove population.